APOE4 genotype associations with longitudinal change in hippocampal microstructure. (20th December 2022) - Zhu, Alyssa H; Nir, Talia M; Gari, Iyad Ba; Dixon, Daniel; Islam, Tasfiya; Villalon‐Reina, Julio E; Thompson, Paul M; Jahanshad, Neda
Abstract: Background: Apolipoprotein E4 (APOE4) is a major risk factor for late‐onset Alzheimer's disease (AD). Associations between APOE4 genotype and hippocampal atrophy have been reported, but few longitudinal studies have evaluated microstructural changes. There is evidence that risk conferred by APOE4 may be partially driven by factors such as cerebral iron burden, neuronal injury, and inflammation. Brain iron concentration and other microstructural properties may be detected in vivo using quantitative susceptibility mapping (QSM) and diffusion‐weighted MRI (dMRI). Here, we characterized the effects of APOE4 genotype on longitudinal changes in hippocampal QSM and dMRI microstructural measures in a population‐based sample of adults from the UK Biobank (UKB). Method: 598 UKB participants of European ancestry (baseline age: 48‐78 years) with baseline and ∼2 year follow‐up brain MRI data were analyzed (Figure 1A ). Four dMRI measures were derived from diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI; Figure 1B ). Median dMRI and QSM hippocampal measures were extracted and averaged across hemispheres. For comparison with microstructure, bilateral hippocampal volume was also estimated. Linear regressions were used to test associations between change in six hippocampal measures (FollowUp‐Baseline) and number of E4 alleles (e3e3/e3e4/e4e4) adjusting for the time‐interval between scans, baseline MRI measure, age, sex, age‐by‐sex, age2, age2‐by‐sex, education, and the first 4 genetic ancestry principal components. Age‐dependent effects were explored in post‐hoc analyses including a sensitivity analysis stratifying associations by age (< 65 or ≥ 65 yrs) and evaluation of APOE4‐by‐age interactions. Result: Compared to e3e3 homozygotes, E4 carriers had significantly greater increases in MD and ISOVF and greater decreases in ND ( p <critical FDR threshold; q =0.05; Table 1 ). E4 carriers ≥65 had nominally greater increases in MD and ISOVF and greater decrease in volume ( p <0.05); APOE4‐by‐age interactions were found for changes in ISOVF and volume ( p <0.05; Figure 2 ). Conclusion: Disease risk conferred by the APOE4 genotype may be linked with greater inflammation (greater diffusivity) or neuronal loss. E4 associations with atrophy were only found in the subset of older participants, suggesting that detection of microstructural changes may precede volumetric changes in the hippocampus.